Endgame : a Nameless Detective novel - Pronzini, Bill (Pronzini, Bill. "Nameless Detective" mysteries., 2017)
The Nameless Detective has taken many cases over the years and this is one for the books. Or rather, two cases that will test his agency's resources. Love is in the air...more to the point, love gone awry. One case involves a woman whose husband died accidentally in a remote cabin in the Sierras. The wife isn't buying that her husband was alone, and is determined to find out his secret and get closure in spite of any potential heartbreak. The other case is a missing person . . . but the person missing was agoraphobic and never left the house. The husband swears that while their relationship was strained due to his wife's condition, he was still in love with her. He begs Nameless to clear him and find his wife before the cops come for him. Bill Pronzini's Endgame is a classic Nameless tale twisty puzzles featuring one of mystery's best loved detectives.